ROUTINE PREOPERATIVE BLOOD GROUP AND SAVE TESTING IS UNNECESSARY FOR ELECTIVE LAPAROSCOPIC CHOLECYSTECTOMY - Tandon, Ashutosh; Shahzad, Khalid; Nunes, Quentin; Shrotri, Milind; Lunevicius, Raimundas (Journal of Ayub Medical College Abbottabad, 2017)
Background: Although the practice of preoperative testing of ABO group and Rh (D) type for elective cholecystectomy has deep historical roots, it is not evidence-based. We aimed to assess the preoperative blood group and save testing practice for a cohort of patients subjected to elective laparoscopic cholecystectomy for symptomatic cholecystolithiasis between January 2010 and October 2014. Methods: National Health Service (NHS) hospital based, surgical procedure-specific, retrospective study was conducted. A final group consisted of 2,079 adult patients. We estimated the incidence of perioperative blood transfusion attributable to laparoscopic cholecystectomy. The results of eight other studies are presented. Results: A preoperative blood group and save test was performed in 907 patients (43.6%), whereas cross-matching was documented in 28 patients (3.1%). None required an intraoperative blood transfusion. Twelve patients (0.58%) underwent blood transfusion postoperatively following laparoscopic cholecystectomy, of which ten were transfused due to severe intra-abdominal bleeding (0.48%). There were no deaths. Conclusions: The likelihood of blood transfusion attributable to elective laparoscopic cholecystectomy is 1:200. A routine preoperative blood group and save testing is unnecessary. It neither alters the management of severe hypovolemia, secondary to perioperative bleeding, nor does it lead to better outcomes. Keywords: Cholecystolithiasis; laparoscopic cholecystectomy; blood group; blood transfusion